2018
DOI: 10.1080/02723638.2018.1500246
|View full text |Cite
|
Sign up to set email alerts
|

Financial market actors as urban policy-makers: the case of real estate investment trusts in Brazil

Abstract: Focusing on the recent growth of Real Estate Investment Trusts (REITs) in Brazil, the paper explores how financializing policy instruments intertwine financial markets and the urban built environment. The paper studies the career of REITs in Brazil since the 1990s and questions the role of financial market actors and capital in urban dynamics. It uncovers three processes that are usually considered separately: i) how a network of public and private financial market actors coaxes state bodies into using their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
20

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 45 publications
(41 reference statements)
0
35
0
20
Order By: Relevance
“…In Lombardy, for example, social-mixing policies were key in aggregating socioeconomic groups with different solvency capacities acting as a social-engineering device to mitigate investment risk. Understanding financial intermediation thus requires refining the policy instrument approach recently employed to examine the financialisation of urban production (Sanfelici and Halbert, 2019) by looking beyond the mere action of financial policy instruments to unpack their interplay with other policy fields, apparently tangent but de facto implicated in financialisation. The point here is not solely to stress the importance of public policies as preconditions for financialisation (Bernt et al., 2017) but to recognise their enduring functional role for financial extraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Lombardy, for example, social-mixing policies were key in aggregating socioeconomic groups with different solvency capacities acting as a social-engineering device to mitigate investment risk. Understanding financial intermediation thus requires refining the policy instrument approach recently employed to examine the financialisation of urban production (Sanfelici and Halbert, 2019) by looking beyond the mere action of financial policy instruments to unpack their interplay with other policy fields, apparently tangent but de facto implicated in financialisation. The point here is not solely to stress the importance of public policies as preconditions for financialisation (Bernt et al., 2017) but to recognise their enduring functional role for financial extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the state has mostly been seen as enabler/facilitator, and its crafting role in shaping financial infrastructures and instruments has been overlooked. By combining the analytical approach focused on policy instruments—tested recently in the study of the financialisation of urban production (Sanfelici and Halbert, 2019)—with a novel trans-scalar perspective, the paper innovatively explores the interplay and distribution of power among different levels of government (in particular, the ‘hinge function’ of neglected intermediate levels) and their intertwining roles, not just as mediators but as active participants in housing financialisation within specific national contexts. In so doing, it also adds to the debate on state financialisation, whereas the Italian case reflects the generalised post-Keynesian tendency of governments to practise ‘statecraft’ by relying on financial innovation (Lagna, 2016: 167).…”
Section: Three Debates On the Financialisation Of Rented Housingmentioning
confidence: 99%
“…Despite the novelty of this scholarship, there are numerous empirical analyses concerning housing financialization in general (Kutz & Lenhardt, 2016 ; Migozzi, 2020 ; Sanfelici and Halbert, 2019 ; Waldron, 2018 ) and rental housing financialization in particular (Aalbers et al, 2017 ; August, 2020 ; August & Walks, 2018 ; Byrne, 2020 ; Crosby, 2020 ; Fields, 2017 ; Fields & Uffer, 2016 ; Teresa, 2016 ; Wijburg et al, 2018 ). Below is a discussion about (a) the geographical coverage within this scholarship (with some other findings) and (b) the expansion of financialization to the developing world.…”
Section: Rental Housing Financializationmentioning
confidence: 99%
“…Case-studies have highlighted how, in the context of urban redevelopment projects, their decisions in landuse regulations, public investment in land and transport, and negotiations with developers -and sometimes local opponents -have contributed to such a process (Charnock et al, 2014;Guironnet et al, 2016;Kaika & Ruggiero, 2016;Savini & Aalbers, 2016;Theurillat & Crevoisier, 2014). Relatedly, other authors have shown how local governments, often faced with decreased funding from the central state and/or their local tax base, have used "financializing policy instruments" (Sanfelici & Halbert, 2019) to tap into capital markets, such as tax increment financing (Pacewicz, 2012;Weber, 2010) and other municipal bonds (Peck & Whiteside, 2016), special purposes vehicles for housing construction (Beswick & Penny, 2018), or public-private partnerships and other infrastructure concessions operated by financial consortiums (Ashton, Doussard, & Weber, 2016). This scholarship has contributed to go beyond central state-centric accounts by demonstrating how "local governments construct a nexus between global financial circuits and local property markets" (Weber, 2010, p. 253), not without scepticism regarding "the possibilities and capabilities of most municipalities to mobilise financial markets to their benefit" (Savini & Aalbers, 2016, p. 879).…”
Section: Global Real Estate Fairs the Elephant In The Room Of Urbanmentioning
confidence: 99%